Low-dose photodynamic therapy promotes vascular E-selectin expression in chest malignancies, improving immune infiltration and tumor control - Sabina Berezowska; Michel Gonzalez; Jean Yannis Perentes; Thorsten Krueger; Michel Christodoulou; Lucas Liaudet; Etienne Meylan; Tereza Losmanová; Louis-Emmanuel Chriqui; Damien Nicolas Marie; Alexandros Sifis; Christophe Gattlen; et al. (Journal for ImmunoTherapy of Cancer)
Background Chest malignancies such as non-small cell lung cancer (NSCLC) or pleural mesothelioma (PM) have an ominous prognosis. Photodynamic therapy (PDT) of NSCLC and PM improves patient survival, but the precise underlying mechanism remains unknown. Here, we hypothesized that low-dose PDT (L-PDT) alters the expression of tumor endothelial cell adhesion molecules favoring immune cell recruitment and tumor control. We explored this hypothesis in two mouse models of NSCLC and PM. We validated our findings in 82 PM patient samples.Methods We assessed, in C56BL/6 mice bearing 344SQ-NSCLC and in BALB/c mice bearing AB12-PM, how L-PDT (400 μg/kg Visudyne administered intravenously, irradiance: 50 mW/cm2, light dose: 10 J/cm2) affected tumor growth, modulated the tumor immune microenvironment and the expression of endothelial selectin cell adhesion molecule (E-selectin) using real-time multiphoton imaging, immunofluorescence staining and flow cytometry. We then blocked E-selectin, canonical nuclear factor kappa B (NF-κB) pathway or selectively depleted CD8+ lymphocytes with dedicated peptides/antibodies in mouse models to evaluate the effect of L-PDT on tumors. Finally, we assessed in 82 PM patient samples the correlation between vascular E-selectin and CD8+ lymphocyte content by immunofluorescence staining of tissue sections and their association with patient survival.Results L-PDT induced vascular E-selectin in both NSCLC and PM, which enhanced granzyme B+/CD3+/CD8+ lymphocyte infiltration and improved tumor control. Blockade of E-selectin or immunodepletion of CD8+ lymphocytes abrogated the L-PDT-mediated cancer regression. Moreover, canonical NF-κB pathway blockade impaired enhanced vascular E-selectin expression and CD8+ T cells infiltration in tumors following L-PDT. In human malignant pleural mesothelioma samples, we found a correlation between vascular E-selectin and CD8+ T cell infiltration, which was associated with improved patient outcome.Conclusion L-PDT remodels the vasculature of chest tumors and favors a cytotoxic immune microenvironment promoting tumor control. This approach could complement current immunotherapy approaches in these malignancies.